Demand For Financial Capital By Smallholder Food Crop Farmers And Disbursement Decisions of Financial Institutions In South-East Nigeria - .A, Okon Xavier-Itam; J.S, Orebiyi; D.O, Ohajianya; U.C, Ibekwe; J.N, Ugwu; .A, Tim- Ashama (IJRDO - Journal of Business Management, 2017)
This study analyzed demand for financial capital by smallholder food crop farmers and disbursement decisions of financial institutions in Southeast Nigeria. The specific objectives of the study were to; determine the demand for financial capital by smallholder food crop farmers, determine the factors affecting the smallholder food crop farmers’ demand for financial capital, and determine factors influencing the financial capital disbursement decisions of the financial institutions with respect to smallholder food crop farmers. Data were collected with validated questionnaire from 360 randomly selected smallholder food crop farmers and 36 purposively selected financial institutions from the three sampled states of South-East Nigeria. Data were analyzed using descriptive statistics, multiple regression techniques, multinomial logit model, and Analysis of variance model. Results showed that mean amount of credit demanded by smallholder food crop farmers was N508,426.39. There were no significant differences in the small holder food crop farmers’ demand for financial capital in the states of South-East Nigeria. Factors affecting small holder food crop farmers’ demand for financial capital were age, education level, farming experience, farm size, annual farm income, annual estimated farm expenditure, level of awareness of financial capital sources, grace period and farmers’ loan transaction cost. The study equally found that farmers’ sex, education level, farming experience, farm size, possession of collateral, dependency ratio, and farm household’s networth were important in the financial capital disbursement decisions of financial institutions to smallholder food crop farmers. Demand for financial capital by smallholder food crop farmers was relatively high. Policies that will strengthen farmers’ capacity to exhibit effective demand for financial capital such as targeted capacity building programmes, credit and farm output price guarantees should be pursued by government.